Internal Migration, Political Efficacy, and Political Participation in Autocracies: Evidence from China - Yuequan Guo; Jiannan Zhao (Political Studies, 2025)
How is internal migration related to political efficacy and participation in autocracies? Existing research emphasizes migration's socioeconomic impact, given the staggering internal migration volume in developing countries, but pays inadequate attention to its relationship with politics. We argue that migrants are more likely to interact with the government and possess greater political efficacy than non-migrants. When migrants return home, they are motivated by higher political efficacy to participate more in politics than non-migrants. We test the theory using four nationally representative surveys in China from 2006 to 2014 and find that returning migrants are more confident in understanding and influencing politics. However, they vote less in elections and avoid challenging the government collectively. Exploratory analysis shows that the counterintuitive results arise because returning migrants shift from traditional political participation, like voting, to new means, like lodging complaints online. The relationship between migration and politics is contingent on the authoritarian context.
Keywords: 320; internal migration; autocracy; political efficacy; political participation; China